Recursos tecnológicos de comunicación y su incidencia en el aprendizaje en niños de tercer año de básica de la Unidad Educativa Juan Montalvo del cantón Buena Fe, año 2022 - Giler Rojas, Evelyn Zulay (2022)
The current investigation was based on the existing problem of the use of technological resources that positively and negatively affect children of basic education of the Juan Montalvo Educational Unit, technological resources are currently of great importance not only for communication between people, but rather helps students to influence better learning. The general objective of the research is to carry out an analysis of the use of technological resources of communication and its impact on the learning of children in the third grade of the Juan Montalvo Educational Unit. The methodology used for the research was based on types: exploratory, documentary, and a case study, where the survey was carried out using the questionnaire as a tool, where the parents of the courses in question present that the technological resources are necessary. for student learning, however; agree that the excessive use of these can affect health problems such as anxiety, lack of socialization with people around them and poor concentration. For this reason, awareness campaigns will be carried out to establish to parents that, if the use of technologies is necessary and that, in addition, on the other hand, they are not necessary.